INVOLVEMENT IN BUSINESS OF YOUNG GRADUATES OF VOCATIONAL EDUCATION AND TRAINING INSTITUTIONS: THE CASE OF THE REPUBLIC OF MOLDOVA - ACULAI, Elena; DELIU, Natalia (Economy and Sociology, 2021)
Young people from the Republic of Moldova, who intend to initiate or to develop their business are one of the targeted support groups within the framework of the state policy. This article analyzes various aspects of engaging young people in entrepreneurial activity: a brief assessment of statistical indicators is given; support measures for young entrepreneurs, implemented by the Moldovan government and proposed by international/foreign organizations are outlined; features of young entrepreneurs and self-employed are revealed. The emphasis is placed on young graduates of Vocational Education and Training (VET) institutions. The main results and conclusions are largely based on a survey applied on graduates of vocational education and training institutions who have already set up their own business or are self-employed. The survey has been implemented during 2016-2017 with the active participation of the authors. The results of the study showed that young people are interested in entrepreneurship and that learning the basics of entrepreneurship has a significant motivating influence on the initiation of their business and self-employment. Often, the businesses of the young people are unregistered and they are combined with employment. Only one third of the respondents know about organizations that can provide them various forms of support. One of the conclusions of the study presents that positive changes can be achieved much faster by combining the efforts of different stakeholders, in this case – the government, educational institutions, non-profit organizations and external donors.